2016
DOI: 10.1021/acs.jpcb.6b08813
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Release of NO from Ruthenium Nitrosyl Ammine Complexes [Ru(NH3)5(NO)]2+/3+ in Aqueous Solution: A Theoretical Investigation

Abstract: In this article, density functional theory in conjunction with Monte Carlo statistical mechanical simulation was used to investigate the electronic structure, reduction potential, solvation, and solvent effects on the electronic spectra of nitrosyl ammine complexes using [Ru(NH)(NO)] as model compounds. In addition, ligand exchange reactions with solvent water molecules were also investigated. It is shown that the complexes are involved in strong hydrogen bonds in aqueous solution, with mean average energies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 78 publications
3
17
0
Order By: Relevance
“…For the Ru III species with d 5 configuration, only the S = 1 / 2 configuration was evaluated since it is the most stable spin state of Ru III complexes. [50][51][52] The optimized Cartesian coordinates of all species studied in this work can be found in the Supplementary Information (SI) section.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the Ru III species with d 5 configuration, only the S = 1 / 2 configuration was evaluated since it is the most stable spin state of Ru III complexes. [50][51][52] The optimized Cartesian coordinates of all species studied in this work can be found in the Supplementary Information (SI) section.…”
Section: Methodsmentioning
confidence: 99%
“…56 We have shown that this combination of methods/basis set provides good reduction potentials for ruthenium complexes. 52 The Gibbs free energy for the interactions involving the Ru II -monoaquo species and the biomolecules (GN3 and GN7 sites, Cys and GSH) were computed using the thermodynamic cycle exemplified in Figure 3 (for the KP1019 monohydrated compound), at the TPSSh/def2-TZVP level of theory.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The presence of this resulting diamagnetic singlet ground state has been further supported by several computational studies. [8][9][10][11] Under these assumptions, the photo-release of the NO· radical depicted in equation 1occurs after a formal electron transfer to the nitrosyl ligand, achieved within an intense low-lying electron transition having a strong charge transfer character towards the strongly withdrawing nitrosyl, in any case.…”
Section: Introductionmentioning
confidence: 99%
“…Their investigation showed that NO coordinates linearly with the NAMI‐A‐HAS adduct, and Ru(III) is reduced to Ru(II). Recent theoretical investigation results published by Rodrigues and Rocha showed that the formation of [Ru(NH 3 ) 5 (NO)] 3+ in its most stable singlet state may take place through at least two singlet–triplet surfaces crossing.…”
Section: Introductionmentioning
confidence: 99%